THE WEST BITUNG SEVENTH DAY ADVENTIST CHURCH MEMBERS VIEW ON SABBATH-KEEPING - Masengi, Randy; Lumingkewas, Edwin (Klabat Theological Review; Vol 4 No 2 (2024): Klabat Theological Review, 2024)
The Sabbath is one of the doctrines of the Seventh Day Adventist (SDA) Church and Sabbath observance is a hallmark of SDA Church members. Members of the SDA Church in West Bitung  have different views regarding Sabbath observance. The purpose of this study is to look at the Biblical basis of Sabbath observance; to know the understanding of conservative, moderate, and liberal views regarding Sabbath observance; and to find out the views of the members of the West Bitung SDA Church on Sabbath observance. The research method used in this research is the implication descriptive method. In analyzing the results of the questionnaire from 270 respondents using descriptive statistical methods. The topics analyzed and discussed in terms of Sabbath observance are understanding the doctrine and practice of Sabbath observance. The conclusions obtained in this study based on the results of the analysis are that in terms of understanding the doctrine, the members of the SDA in the West Bitung area have a conservative view; while for the practice of keeping the Sabbath, the members of the SDA Church in West Bitung have a moderate view. Keywords : Sabbath, Conservative, Moderate, SDA, West Bitung.